Предмет: Математика,
автор: annabo34
(x - y) + (x + y) - (2.x + y); ПОЖАЛУЙСТА ОЧЕНЬ НАДО
Ответы
Автор ответа:
1
Ответ: -у
Пошаговое объяснение:
(х+у) + (х-у) - (2х + у) = х + у + х - у - 2х - у = -у
danil7899:
Tupoydaun01 можешь мне помочь?
Автор ответа:
2
(x - y) + (x + y) - (2.x + y)=x-y+x+y-2x-y=-y
Похожие вопросы
Предмет: Биология,
автор: abu793
Предмет: Русский язык,
автор: qwe123wsxqqwe
Предмет: Другие предметы,
автор: vladislavkuzel47
Предмет: География,
автор: tasha0313
Предмет: Математика,
автор: 21091987